Epigenetic remodeling in insect immune memory - Mukherjee, Krishnendu; Dobrindt, Ulrich (Frontiers in Immunology, 2024)
The innate immune system of insects can respond more swiftly and efficiently to pathogens based on previous experience of encountering antigens. The understanding of molecular mechanisms governing immune priming, a form of immune memory in insects, including its transgenerational inheritance, remains elusive. It is still unclear if the enhanced expression of immune genes observed in primed insects can persist and be regulated through changes in chromatin structure via epigenetic modifications of DNA or histones, mirroring observations in mammals. Increasing experimental evidence suggests that epigenetic changes at the level of DNA/RNA methylation and histone acetylation can modulate the activation of insects' immune responses to pathogen exposure. Moreover, transgenerational inheritance of certain epigenetic modifications in model insect hosts can influence the transmission of pre-programmed immune responses to the offspring, leading to the development of evolved resistance.Epigenetic research in model insect hosts is on the brink of significant progress in the 2 mechanistic understanding of chromatin remodeling within innate immunity, particularly the direct relationships between immunological priming and epigenetic alterations. In this review, we discuss the latest discoveries concerning the involvement of DNA methylation and histone acetylation in shaping the development, maintenance, and inheritance of immune memory in insects, culminating in the evolution of resistance against pathogens.